Working towards safer surgery in Africa; a survey of utilization of the WHO safe surgical checklist at the main referral hospitals in East Africa. Issue 1 (December 2015) - Epiu, Isabella; Tindimwebwa, Jossy; Mijumbi, Cephas; Ndarugirire, Francois; Twagirumugabe, Theogene; Lugazia, Edwin; Dubowitz, Gerald; Chokwe, Thomas
Abstract Background Mortality from anaesthesia and surgery in many countries in Sub-Saharan Africa remain at levels last seen in high-income countries 70 years ago. With many factors contributing to these poor outcomes, the World Health Organization (WHO) launched the "Safe Surgery Saves Lives" campaign in 2007. This program included the design and implementation of the "Surgical Safety Checklist", incorporating ten essential objectives for safe surgery. We set out to determine the knowledge of and attitudes towards the use of the WHO checklist for surgical patients in national referral hospitals in East Africa. Methods A cross-sectional survey was conducted at the main referral hospitals in Mulago (Uganda), Kenyatta (Kenya), Muhimbili (Tanzania), Centre Hospitalier Universitaire de Kigali (Rwanda) and Centre Hospitalo-Universitaire de Kamenge (Burundi). Using a pre-set questionnaire, we interviewed anaesthetists on their knowledge and attitudes towards use of the WHO surgical checklist. Results Of the 85 anaesthetists interviewed, only 25 % regularly used the WHO surgical checklist. None of the anaesthetists in Mulago (Uganda) or Centre Hospitalo-Universitaire de Kamenge (Burundi) used the checklist, mainly because it was not available, in contrast with Muhimbili (Tanzania), Kenyatta (Kenya), and Centre Hospitalier Universitaire de Kigali (Rwanda), where 65 %, 19 % and 36 %, respectively, used the checklist. Conclusion Adherence to aspects of care embedded in the checklist is associated with a reduction in postoperative complications. It is therefore necessary to make the surgical checklist available, to train the surgical team on its importance and to identify local anaesthetists to champion its implementation in East Africa. The Ministries of Health in the participating countries need to issue directives for the implementation of the WHO checklist in all hospitals that conduct surgery in order to improve surgical outcomes.